TRANSFORMATION AND SCATTERING OF SURFACE WAVES ON THE ACOUSTIC LOAD TO ULTRASONIC EVALUATION AND MEASUREMENTS. Part 1. The boundary of acoustic contact is sliding - A. R. Baev; F. I. Panteleenko; V. V. Zakharenko; G. I. Razmyslovich; K. G. Lark; N. N. Gil (Приборы и методы измерений, 2018)
for the enhancement and improvement of ultrasonic methods evaluation and measurements. The purpose of this work is to determine the influence of the geometric parameters of the acoustic load body and its position on the coefficients of reflection and propagation of the Stoneley and Rayleigh waves and to identify the possibility of using the results of the study for practical applications.Based on the analysis of the acoustic path and the experimental data, the relationship between the measured amplitude parameters and the coefficients of the propagation and reflection of surface waves, as well as the reflectivity of the contact region of the load body in the form of a prism through the sliding boundary, which reaches up to ≈ 32–34 дБ, is established. For the first time, the dependence of these coefficients on the inclination angle of one of the prism lateral faces in the range of 0 ± 45°, dimensionless thickness of the contact layer (0–0,05) and its orientation relative to the acoustic axis.It is established that these coefficients are mainly maximal when the prism is rectangular. The coefficient of reflectivity in the hard contact of bodies is more than an order of magnitude less, and the coefficients of wave propagation – comparable in magnitude. The prospects of using the results of the study to evaluate the quality of adhesion of materials during welding, soldering, gluing, detection of defects in hardto-reach places, as well as to determine the physical and mechanical properties of metals by the proposed method of creating a reference signal are shown.